Analisis Pembangunan Ekonomi dan Sektor Pariwisata di Desa Ngebel - Dita Putra Pratama; Sudarmiani Sudarmiani; Dwi Nila Andriani (Universitas PGRI Madiun, 2021)
This study aims 1) to determine how economic development and the tourism sector in Ngebel Village, Ngebel District, Ponorogo Regency; 2) to determine the supporting and inhibiting factors of economic development and the tourism sector; 3) to determine the role of local governments in increasing economic development and the tourism sector; 4) to determine the role of the community in increasing economic development and the tourism sector; 5) as well as to determine the impact of the development of the Ngebel Lake tourism object in economic development in Ngebel Village, Ngebel District, Ponorogo Regency. This study uses qualitative research methods with descriptive types to analyze economic development and the tourism sector. Sources of research data obtained through primary data and secondary data. Primary data is in the form of sources with a total of 22 informants and secondary data uses journals, internet and evidence of records. The research instruments used were interview and observation guidelines. Data collection techniques using literature study and field studies. Data analysis techniques use data reduction (data reduction), data display (data presentation) and verification. The research uses research procedures or steps in the form of building a conceptual framework, formulating research problems, selecting subjects, developing instruments, collecting data, analyzing data and matrices and testing conclusions. The results or findings show that economic development and the tourism sector in Ngebel Village were carried out very well. The role of the village government and the community is very influential in increasing economic development and the tourism sector in Ngebel Village. Tourism development has a very positive impact on society, especially in terms of the economy